Novel Molecules in Diabetes Melitus, Dyslipidemia and Cardiovascular Disease (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The purpose of this reprint based on the Special issue "Molecules in Diabetes Melitus, Dyslipidemia and Cardiovascular Disease”, IJMS journal, MDPI, is to present the impact in clinical practice as well as in medical research of novel molecules that have been introduced in the treatment of diabetes mellitus, dyslipidemia, and cardiovascular disease.